Kompetencja leksykalna nastoletnich użytkowników języka polskiego jako odziedziczonego i ojczystego w ujęciu komparatywnym - Seretny, Anna (Neofilolog, 2024)
Lexical competence of teenage heritage and native users of Polish has never been the subject of a comprehensive comparison. The first extensive empirical data were gathered by the Jagiellonian University research team in the project Heritage and native language – a comparison of language competences of teenage Polish and heritage learners. In the first stage of the present study, vocabulary tests of the two groups were analyzed. The results showed few differences in receptive knowledge, but in productive knowledge heritage users lagged behind. Therefore, in the second stage, selected essays were compared in terms of their vocabulary profiles. It was found that native and heritage language users’ lexical profiles differ markedly, to the considerable disadvantage of heritage users. Polish educators responsible for the schooling of migrant children must be aware of this, as too often heritage speakers who enter home schools after (re)immigration are treated as if there were native users. This however, as this research has clearly shown, is by no means the case.